THE MODEL OF ORGANIZATIONAL COMMITMENT AND ITS IMPLICATIONS ON THE LECTURER PERFORMANCE - Hasanah, Hasanah; Madiistriyatno, Harries (Dinasti Publisher, 2020)
The aim of this research was to find out and to analyze both partially and simultaneously the influence of leadership style, competency, work discipline and organizational commitment toward the performance of lecturer. The research methods were descriptive and verificative used to test the hypothesis. The populations in this research were 410 lecturers, and samples were taken by proportionate random sampling on 260 lecturers, data collection was through questionnaires. The hypothesis test was using Structural Equation Modelling or SEM) with application program of LISREL 8.70. The result of this research was processed by 2nd CFA (Second Order Confirmatory Factor Analysis). The result of the research explained that the organizational commitment variable mediated three variables of leadership style, competency and work discipline of the lecturer performance. Thus organizational commitment variable was as full mediating, the most dominant variable which influenced the lecturer performance was the organizational commitment especially affective commitment dimension.